THE SYSTEM OF AUTOMATED AVOIDANCE OF HAZARDOUS SITUATIONS AT AIRCRAFT APPROACH BEFORE GLIDESLOPE DESCENT - A. I. Eremin; G. N. Lebedev; I. A. Chekhov (Научный вестник МГТУ ГА, 2016)
The article presents the attitude to the organization of continuous predictive control of approach safety under the hypothesis about the optimal behavior while eliminating dangerous situations. The task solution of the optimal control and monitoring based on dynamic programming as well as a computer modeling procedure of the present process has been given. Computer modeling showed that under an inactive or delayed control the risk function increases considerably. Some attention was drawn to the problem of the correct choice of the threshold for the risk function, using the results of computer simulation for this purpose. The solution of the problem was obtained under the assumptions of stationary optimal control and simplified flight dynamics.